2013
DOI: 10.1038/nprot.2013.072
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-based receptor identification on living cells and tissues using TRICEPS

Abstract: Physiological responses to ligands such as peptides, proteins, pharmaceutical drugs or whole pathogens are generally mediated through interactions with specific cell surface protein receptors. Here we describe the application of TRICEPS, a specifically designed chemoproteomic reagent that can be coupled to a ligand of interest for the subsequent ligand-based capture of corresponding receptors on living cells and tissues. This is achieved by three orthogonal functionalities in TRICEPS-one that enables conjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
0
65
0
Order By: Relevance
“…No specific protein was selectively captured as determined by MS analysis, leading us to speculate that NP41 bound with low affinity to homogenates. Thus, to capture NP41-receptor interaction in situ, we developed a method for proximity labeling ligand-bound proteins using photooxidation and targeted BH labeling and also tested previously described glycoprotein capture using TRICEPS-based chemistry (8,9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No specific protein was selectively captured as determined by MS analysis, leading us to speculate that NP41 bound with low affinity to homogenates. Thus, to capture NP41-receptor interaction in situ, we developed a method for proximity labeling ligand-bound proteins using photooxidation and targeted BH labeling and also tested previously described glycoprotein capture using TRICEPS-based chemistry (8,9).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of methods to capture native ligand-receptor interactions have used chemical or photo-cross-linking followed by mass spectrometry (MS), some requiring that ligands retain binding activity after potentially disruptive chemical treatment (6)(7)(8)(9). In most cross-linking techniques, the ligand must reach an appropriately reactive site on the target for cross-linking to occur, while being conjugated to a potentially bulky purification tag, which can weaken specific binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TriCEPS reagent is a proprietary trifunctional molecule with three key moieties: (i) an amine-reactive group capable of binding a peptide ligand of interest, (ii) a cross-linking group capable of bonding to oxidized glycans, and (iii) an affinity tag for downstream extraction (20,50). These studies were performed by DualSystems Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…have recently shown that ligand-directed crosslinking using their TRICEPS crosslinker is an effective method for the identification of cell surface binding partners for soluble protein ligands23. In the TRICEPS method, soluble ligands are labelled with the trifunctional TRICEPS crosslinker through an amine reactive group and crosslinks are formed following binding of the labelled ligand to oxidized cells or tissues via hydrazone bond formation between a protected hydrazide group on the TRICEPS crosslinker and aldehyde-containing glycans on the cell surface receptor45.…”
mentioning
confidence: 99%